A scoping review of 2018–2020 research on NCDs and physical activity in Ghana: Groundwork for a monitoring system and action plan - Nyawornota, V.K.; Tay, D.A.; Adu, E.; Ocansey, R.T.A. (John Wiley & Sons, 2022)
Background Physical inactivity is a risk factor for chronic noncommunicable diseases (NCDs), yet national surveillance of physical activity (PA) levels is not well defined. Though Ghana has a national health policy that emphasizes health promotion and prevention of lifestyle diseases, and an NCD policy with PA recommendations in 2012, it does not have an integrated plan of action to address widespread physical inactivity. Objective This review aims to identify the nature and extent of research in NCDs and PA in Ghana to inform the creation of an integrated action plan to address physical inactivity. The review focuses on four research questions: (1) what is the prevalence and monitoring of NCDs in Ghana from the Demographic and Health Survey (DHS) and the World Health Organization (WHO) reports, (2) what are the key risk factors of NCDs in Ghana, (3) what are the identified indicators and benchmarks that enhance or impede PA participation in Ghana, and (4) what are the active interventions and policy directives for NCDs and PA participation in Ghana. Methods Ghana-specific articles, reports, and policies related to NCDs and PA were collected traversing 2018–2020. The scoping review included: (1) reviewing articles and documents related to risk factors of NCDs in Ghana, (2) reviewing articles and documents from the Global Observatory for Physical Activity (GoPA!) monitoring and surveillance template for Ghana; (3) reviewing articles and documents on the Active Healthy Kids Global Alliance Ghana Report Card on Physical Activity; (4) the Demographic and Health Survey website and (5) specific searches for World Health Organization reports. Results A total of 1763 records were identified through keyword search. Based on eligibility criteria, 4 were relevant to question 1, 23 to question 2, 16 to question 3, and 11 to question 4. For question 1, international benchmark surveys revealed that physical inactivity accounts for 20% of NCD related deaths in Ghana. For question 2, 8 records (34.8%) focused on hypertension, 5 (21.74%) body composition and obesity, 4 (17.4%) cardiovascular diseases, 3 (13.0%) on diabetes, 1 (4.4%) on stroke, and 2 (8.7%) on other risk factors. For question 3, 6 records (37%) focused on overall PA, 3 (19%) on the built environment, 2 (12%) active transportation, 2 (12%) on physical inactivity or sedentary behaviors, 2 (12%) on influence of family and peers, and 1 (6%) on active play. For question 4, though multiple national policies exist, including a minimum weekly level of compulsory physical education per week in the school curriculum, data monitoring and surveillance on PA participation are scarce. Conclusion Based on the scoping review of articles traversing 2018–2020, this review revealed minimal research on these topics. Data on PA participation is non-existent due to lack of conscious monitoring mechanisms, integrated plan of action, intervention strategies and policy directives. A national research agenda is imperative to better understand the relationship and clear connection between physical inactivity as a risk factor of NCDs.
Research Article